Fruits and their uses in Mesopotamia light of published Cuneiform texts - Abid Al-Ameer Jassim, Jassim (Al-Adab Journal, 2021)
The importance of studying the theme of Fruits and its benefits in Mesopotamia light of published Cuneiform texts is of great importance in the lives of the population. Fruits were not only for food, but were also included in many daily biological aspects, including food industries, herbal uses and exorcism. The evil and the elimination of magic and decorations were used in architecture and to reduce the effects of the environment, and the importance of the subject matter and the breadth of information. The study was limited to specific examples of fruit fruits, which included time, figs, vines and apples, with the names of other fruits mentioned in a special table based on letters, theses and the most important Dictionaries for the applicable signs, the most prominent of which are (CAD, MDA, AHw, ŠDG, CDLI).